Bread‐baking quality and the effects of Glu‐D1 gene introgressions in durum wheat (Triticum turgidum ssp. durum). Issue 6 (17th August 2021) - Morris, Craig F.
Abstract: Background and objectives: Durum wheat ( Triticum turgidum ssp. durum ) (2 n  = 28, AABB) utilization is somewhat hampered by its weak and/or inextensible gluten. One strategy to overcome this limitation is through the introduction of the Glu‐D1 alleles from bread wheat ( Triticum aestivum ) (2 n  = 42, AABBDD). Findings: Several methods have been employed to introduce or transfer the Glu‐D1 locus into durum wheat. These have included whole chromosome additions of 1D, substitutions of 1D for 1A or 1B, spontaneous and Ph1b ‐induced homoeologous recombination of bread wheat chromosome 1D with the 1A or 1B of durum, and genetic transformation using Glu‐D1 Dx and Dy genes singly or together. Conclusions: The introduction of whole 1D chromosomes has three main drawbacks: (a) instability of the n  = 30 chromosome addition lines, (b) agronomic inferiority of 1D substitutions, and (c) lack of homologous pairing of 1D in subsequent breeding. Genetic transformation has shown limited utility as gene insertion and inheritance are not predictable, and consumer acceptance of genetically modified organisms is not widespread. Consequently, homoeologous recombination appears to be the most promising approach. Key considerations include (a) size of the 1D translocation, (b) substituted (loss, replacement) of a portion of 1A or 1B, and (c) utilization of Dx2 + Dy12 versus Dx5 + Dy10, or other possible Glu‐D1 alleles. In general, the introduction of Glu‐D1 increased dough strength and bread‐making quality. Glu‐D1 Dx2 + Dy12 seemed superior to Dx5 + Dy10, as the latter produced excessively strong, inelastic doughs. Significance and novelty: Durum wheat production and consumption will increase as bread quality improves. The Glu‐D1 high molecular weight glutenin proteins will likely play a role in improving bread‐making ability.